O envelhecimento humano na periferia : um diálogo entre idosos moradores da periferia e a perspectiva da psicologia do desenvolvimento do curso de vida, lifespan - Lichtenfels, Henriete (2007)
The getting old process with wellness is a continous learning process with daily search for life sense and existencial renovation. This dissertation discusses the perspective of the so-called lifespan development theory, which understands human development as a process that takes place throughout life. It does so by establishing a dialog with elderly people who live in two neighborhoods located in the outskirts of Porto Alegre, the capital of the state of Rio Grande do Sul, Brazil. The lifespan development model advocates a diluted view of chronological age and is not coupled with normative stages. It is determined by biological, sociocultural, historical and personal aspects. According to this model, human development occurs at a different speed and rhythm for each elderly person. Growing old in a satisfactory manner implies the use of three processes: selection, optimization and compensation. These are strategies for choosing goals and actions designed to achieve them that stimulate the elderly in their capacity for resistance, plasticity and flexibility. They are management strategies for a life with well-being. The author made use of qualitative research and the phenomenological approach when interviewing 30 senior citizens between 62 and 82 years of age who get together to socialize in groups or receive health care services at stations maintained by the Moinhos de Vento Hospital Association. They all live in the neighborhoods called Morro da Cruz and Ilha Pintada. Most of them are women, 68% live with family members, sharing small houses, 44% are illiterate or can hardly read. The number of children is high among the elderly with less education: up to 14 children. According to their own perception of their aging process, most of them think that they are in a better situation now. They feel happier and less tired, although almost all of them report one or more pathologies and comorbidities. The study examined the use of selection, optimization and compensation strategies by the elderly in their daily lives, showing the importance of the choices made by most of them, in spite of the constraints imposed on them by the poverty they experience in socioeconomic and cultural terms. When they are able to choose and optimize some meaningful action related to socializing, working or learning, they show more happiness and satisfaction with their lives. They are masters at compensating because their situation of deprivation is part and parcel of their life experience. Understanding aging as a constant new beginning that opens up possibilities of making choices in old age is a contribution toward turning the elderly into citizens.